Post-hoc analysis of single nucleotide polymorphism profile for eyes with vascularized pigment epithelial detachment due to ARMD. Issue 3 (May 2021) - Lee, Daniel; Chan, Clement K; Abraham, Prema; Sarraf, David
Introduction: This post-hoc case-control study compares single nucleotide polymorphism (SNP) profile of eyes with vascularized pigment epithelial detachment (vPED) due to age-related macular degeneration (ARMD) with: (1) Control-1 eyes (no ARMD and AREDS Severity Scale 0); and (2) Control-2 eyes (drusen or AREDS Severity Scale 2). SNP profile of High Responders (HR) was also compared with Low Responders (LR) to ranibizumab. Methods: Blood samples from 40 patients with vPED treated with ranibizumab were sent for SNP-specific genotype analysis for comparison of variant allele frequencies of 23 SNPs associated with ARMD (VAF) to VAF in 184 Control-1 eyes, and VAF in 85 Control-2 eyes. VAF of HR-50 (⩾50% decrease in PED height) and VAF of HR-75 (⩾75% decrease in PED height) were also compared with VAF of LR. Results: These SNPs were more frequent in vPED than Control-1 eyes: APOE rs4420638 (A/G), HTRA1 rs104904924 (G/T), VEGF rs943080 (T/C), CFH rs1061170 (T/C), CFH rs2274700 (C/T), CFH rs10737680 (A/C), CFH rs10801555 (G/A). These SNPs were more frequent in vPED than Control-2 eyes: APOE rs4420638 (A/G), CFI rs4698775 (G/T), COL15A1/TGFBR1 rs334353 (T/G). FRK rs3812111 (T/A) was more frequent in HR-50 and HR-75 eyes compared with LR. Conclusion: Seven SNPs were more frequent in vPED eyes than non-ARMD eyes, and three SNPs were more frequent in vPED eyes than drusen eyes. Adjusting for multiplicity, only CFH rs2274700 (C/T) was significant for first comparison, and only COL15A1/TGFBR1 rs334353 (T/G) was significant for second comparison. APOE rs4420638 (A/G) was the single SNP more frequently linked to vPED eyes for both comparisons. FRK rs3812111 (T/A) was consistently associated with high responders.